STRUCTURE AND LOGISTICS DETERMINATION OF THE COMPETITIVE POTENTIAL OF AGRICULTURAL ENTERPRISES - STADNYK, Valentyna; YOKHNA, Vitaliy; GEYDAROVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the conditions of high turbulence of modern agrarian markets, the development of the competitive potential of agricultural enterprises is of key importance in maintaining the export capacity of Ukrainian agribusiness. The article examines the structure of the competitive potential of agricultural enterprises, highlighting the role of each component in the formation of competitive advantages by the enterprise. It is substantiated that competitive potential is a complex system that includes resource, technological, innovation-digital, logistical, organizational-management, marketing and export-institutional components. Each structural component and its functional purpose are characterized. Based on the allocation of competitive advantages that an agricultural enterprise receives from the effective development of competitive potential, the dominant and integrative role of the logistics component of the competitive potential of agricultural enterprises in the implementation of the tasks of development and increasing their market opportunities in the conditions of the destruction of traditional markets is logically proven. Special attention is paid to digital tools for logistical support of production and sales activities of agricultural enterprises, including TMS, WMS, SCM systems, blockchain and traceability platforms, IoT and GIS/GPS monitoring technologies, Big Data analytical solutions and ERP modules. It is shown that their comprehensive implementation ensures the optimization of material flows, reduction of logistics costs, increase of transparency and quality of products, strengthening of adaptability to market changes and increase of operational stability of agricultural enterprises. It is proved that the digitalization of logistics is becoming a key factor in the formation of long-term competitive advantages and strengthening of positions in domestic and foreign agricultural markets. The results of the study confirm the need for strategic development of digital logistics infrastructure as a key element in increasing the competitiveness of agricultural business in the face of growing global challenges.
Keywords: market transformation; accounting support; competitiveness; structural components of competitive potential; digital logistics tools; competitive advantages